A Macro-Distinct Element Model (M-DEM) for simulating the in-plane cyclic behavior of URM structures. (15th January 2021) - Malomo, Daniele; DeJong, Matthew J.
Highlights: New Macro-Distinct model for low-cost simulation of in-plane-loaded URM structures. First macro model ever implemented in the Distinct Element Method framework. URM members idealized as an assembly of FE blocks connected by nonlinear springs. Novel compression model developed to represent crushing phenomena within FE blocks. Models adequately predicted experimental hysteretic responses and crack patterns. Abstract: In this work, a new Macro-Distinct Element Model (M-DEM) for the analysis of the in-plane behavior of unreinforced masonry (URM) structures, aimed at combining the efficiency of simplified approaches with the accuracy of discontinuum-based micro-modeling methods, is presented and validated through comparison against a number of both experimental and numerical tests on URM components. In the M-DEM framework, Finite Element (FE) homogenized macro-blocks are connected by discrete spring interfaces, whose layout is determined a priori as a function of the masonry texture. In-plane diagonal and sliding shear failure mechanisms, as well as flexural damage, are accounted for by the discrete spring interfaces. Meanwhile, a new methodology to simulate crushing, which makes use of a strain-softening model originally conceived for modeling concrete failure, is proposed and calibrated against small-scale tests on masonry samples. The strategy is to simulate shear/tension failure in the block interfaces and compression failure within the FE macro-blocks, while discretizing to allow the possibility of simulating out-of-plane failure modes. Using the M-DEM, the observed experimental damage and the hysteretic behavior of various reduced-scale URM specimens, subjected to shear-compression cyclic loading, were satisfactorily reproduced numerically. The capabilities of the M-DEM to predict the influence of the bond pattern on the monotonic behavior laterally-loaded URM piers were also scrutinized through comparison with standard micro-modeling outcomes, focusing on potential differences concerning both accuracy and computational expense. Finally, given the encouraging results obtained, the proposed approach was extended to the simulation of the in-plane cyclic response of a full-scale URM façade. Although the model marginally underestimated the energy dissipation in the first test phases, a good agreement was obtained in terms of peak and residual base shear capacity, initial in-plane stiffness and its progressive deterioration, governing failure mechanisms and final crack pattern, whilst simultaneously keeping computational costs within acceptable limits.